Facies Characteristics and Depositional Environment Reconstruction of the Minahaki Formation, “DM” Field, Banggai Basin - Sayaf, Ival Umar; Isnaniawardhani, Vijaya; Muljana, Budi; Suganda, Wingky (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
The Miocene Minahaki Formation in the Banggai Basin represented a key hydrocarbon reservoir, but its pronounced heterogeneity posed a challenge for field development. This study aimed to characterize the formation's carbonate facies and reconstruct its depositional environment in the “DM” field to establish a predictive model for reservoir distribution. The research employed an integrated subsurface analysis of core, cuttings, and wireline log data from seven wells. Four principal lithofacies (Bioclastic Coralline Floatstone, Dolomitic Algae Bioclastic Packstone, Argillaceous Dolomitic Foraminifers Bioclastic Wackestone, and Bioclastic Wackestone) were identified and subsequently grouped into two distinct facies associations: a high-energy Reef Margin Complex (FA-1) and a lower-energy Fore-Reef Slope (FA-2). Spatial correlation of these associations revealed a clear proximal-to-distal environmental gradient from west to east. The depositional architecture of the Minahaki Formation in the study area was interpreted as a rimmed carbonate platform. This model accounts for the observed reservoir heterogeneity, concluding that higher-quality reservoir bodies, characterized by moldic, vuggy, and intercrystalline porosity, are concentrated within the single reefal buildup that defines the western margin of the field. This finding provides a direct, geology-based predictive tool for optimizing future drilling activities and serves as a useful analogue for similar carbonate systems elsewhere.